Examen Especial a las fases preparatoria, precontractual, contractual y ejecución para la Adquisición de Bienes y Servicios bajo régimen especial del GAD Municipal Riobamba, período 2019. - Pastuizaca Armijos, Katherin Lisbeth (2022)
The objective of this investigation is to carry out a Special Examination of the preparatory, pre-contractual, contractual and execution phases for the acquisition of goods and services under the special regime of the Riobamba Municipal GAD, period 2019. Due to the fact that the institution has been immersed in several actions control exercised by the Comptroller General of the State as a control body to the different processes of public purchases carried out by the entity, for which a deductive and inductive methodology was applied and a field and documentary investigation was carried out through the application of an interview itself that allowed identifying the most significant weaknesses of the analyzed component. The results that were obtained after the application of the special examination were the following: non-compliance with the legal regulations applicable to the publication of the reforms of the Annual Contracting Plan (PAC) in the portal of the Official System of Public Contracting of Ecuador (SOCE) of the processes of acquisition of spare parts or accessories carried out under the special regime modality. In addition, it was identified that there are repeated deficiencies in the publication of special regime contracts in the public procurement portal. For which, the report is attached in which it contains comments, conclusions and recommendations of the aforementioned findings.